Esthétique de synthèse : dans la matière et les supports de médias numériques narratifs - Everardo Reyes (Cahiers de Narratologie)
This paper uses the notion of synthetic aesthetics to group creative productions that take advantage of the digital properties of media applied to narrative such as interactivity, generativity, la spatiality, and procedurality. The domain of the digital art is investigated through the variety of some forms and formats that have been developed. In this respect, the article builds on the definition of media in its broadest sense, that is as an extension of human beings, and it considers studying digital tools as communicative environments. This contribution presents an overview of tools and methods for creative production and highlights the importance of an experimental practice in digital narrativity.